All‐Soft and Stretchable Thermogalvanic Gel Fabric for Antideformity Body Heat Harvesting Wearable. Issue 44 (13th October 2021) - Ding, Tianpeng; Zhou, Yi; Wang, Xiao‐Qiao; Zhang, Chen; Li, Tongtao; Cheng, Yin; Lu, Wanheng; He, Jiaqing; Ho, Ghim Wei
Abstract: Currently, "wearable thermal‐electric harvester" is a loose term for technology that embraces rigid thermoelectric leg incorporated flexible substrates. In reality, they are not exclusively flexible, much less totally soft and stretchable. Likewise, conventional substrate‐dependent thermogalvanic cells lack the highly sought after mechanical adaptability, and hinder the full exploitation of the inherent merit of their fluidic matrices. The existence of the substrate causes poor air permeability and worse still, leads to low heat transfer efficiency. Here, a soft and stretchable thermogalvanic fabric directly woven out of p/n alternating hydrogel‐based fibers is proposed. In addition to improved wearing comfort, the compliant mechanical properties of the thermogalvanic fabric possess desired adaptability to irregular and continuously deformed skin, so as to realize conformal and efficient body heat harvesting. The scalable and modular, processable soft gel serves as the groundwork to the realization of prototypical arbitrary fabric design and potentially a new battery‐free bodily heat harvesting wearable. Abstract : Substrate‐free thermogalvanic gel fibers with superior electrical and mechanical properties are devised via a scalable and modular based fabrication strategy. Such hydrogel‐based thermogalvanic fabric with highly desired stretchability and elasticity can be directly applied to the irregular surface of the human body, and is capable of sustaining curvilinear and dynamic human body motion for antideformity thermal energy harvesting.